PP-021 Validation and implementation of an analytical quality control method in preterm parenteral nutrition. (24th February 2014) - Lopez-Cabezas, C; Lombraña, M; González, B; Bedini, JL; Guerrero, L; Codina, C
Abstract : Background: Parenteral nutrition (PN) solutions are complex unlicensed medicines that cover essential needs in preterm infants. PN safety must be guaranteed by a proper quality control system. Purpose: To evaluate the feasibility of adapting a routine analytical technique for measuring glucose and electrolytes in plasma and urine for use as a quality control method for preterm PN solutions. Materials and methods: The emergency laboratory uses an automatic chemistry system (DimensionEXL) with spectrometry and indirect potentiometry for the analysis of glucose and electrolytes in plasma and urine. The technique was validated using standard solutions to study glucose, sodium, potassium, calcium and magnesium in a fat-free PN substrate. Simultaneously, we studied the systematic error due to volumetric devices used in the compounding process. Once we knew the accuracy limits of the technique, we discussed with clinicians the clinical significance of differences between theoretical and measured values in order to establish acceptability ranges. Results: Glucose, potassium and calcium values measured in the PN solution correlated well, with readings within 10% of the theoretical. So, we assumed that values out of this range were due to preparation errors. Readings for sodium and magnesium differed by >15% from the calculated values, probably due to a matrix interference. Systematic error due to volumetric devices was considered irrelevant (<5%). The technique was implemented in clinical practice in May 2013. From then, 260 PN solutions have been analysed corresponding to 61 patients, with a mean time response of 55 min. Two preparation mistakes have been detected so far, related to glucose and calcium concentration respectively. Mean cost per unit analysed is 0.25 €. Conclusions: The implementation of an analytical control for preterm PN solutions into the routine practice of the Emergency laboratory has provided a reliable quality control method. They check 100% of samples and know the results before the PN is administered at a very low cost. No conflict of interest.